2020
DOI: 10.1038/s41467-020-17144-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into mitochondrial β-barrel outer membrane protein biogenesis

Abstract: In mitochondria, β-barrel outer membrane proteins mediate protein import, metabolite transport, lipid transport, and biogenesis. The Sorting and Assembly Machinery (SAM) complex consists of three proteins that assemble as a 1:1:1 complex to fold β-barrel proteins and insert them into the mitochondrial outer membrane. We report cryoEM structures of the SAM complex from Myceliophthora thermophila, which show that Sam50 forms a 16-stranded transmembrane β-barrel with a single polypeptide-transport-associated (POT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 71 publications
2
71
0
Order By: Relevance
“…The SAM pathway has been described in detail in another review [ 33 ]. The human SAM complex consists of accessory subunits MTX2 (yeast Sam35), MTX1, and MTX3 (yeast Sam37) and OMM associated β-barrel core subunit SAM50 (yeast Sam50; Table 1 ) [ 34 ]. In yeast, β-barrel precursor proteins are translocated through the TOM complex, where they are bound by small TIM chaperones and transferred through the IMS to the SAM complex ( Figure 1 ).…”
Section: Protein Translocationmentioning
confidence: 99%
“…The SAM pathway has been described in detail in another review [ 33 ]. The human SAM complex consists of accessory subunits MTX2 (yeast Sam35), MTX1, and MTX3 (yeast Sam37) and OMM associated β-barrel core subunit SAM50 (yeast Sam50; Table 1 ) [ 34 ]. In yeast, β-barrel precursor proteins are translocated through the TOM complex, where they are bound by small TIM chaperones and transferred through the IMS to the SAM complex ( Figure 1 ).…”
Section: Protein Translocationmentioning
confidence: 99%
“…A recent study shows that Por1 depletion did not decrease the abundance of carrier protein precursors translocating across the OMM. Rather, the depletion led to decreased integration The TOM complex and the components of the Sorting and Assembly Machinery (SAM) complex are necessary for the biogenesis and the integration of VDAC into the OMM [47]. The depletion of Sam50, the β-barrel integrase of the SAM complex, led to improper integration and function of Por1 in the yeast.…”
Section: Figurementioning
confidence: 99%
“…After crossing through the channel formed by Tom40, proteins that adopted a β-barrel structure are bound to small TIM proteins in the IMS (i.e., Tim9 and Tim10) [ 23 , 24 ] and delivered to the TOB/SAM complex. The TOB/SAM complex consists of two peripheral membrane proteins exposed to the cytosol, namely Tob38 (also known as Sam35) and Tob37 (also known as Sam37/Mas37), as well as the channel-forming protein Tob55/Sam50 [ 25 , 26 , 27 , 28 , 29 ]. Thus, the TOB/SAM complex recognises β-barrel proteins and assists their membrane insertion and assembly [ 3 , 30 ].…”
Section: Overview Of the Mitochondrial Protein Import Machinerymentioning
confidence: 99%
“…The TOB/SAM complex remains in dynamic interactions with other complexes, including TOM [ 80 , 81 ], MICOS (e.g., [ 82 ]) and ERMES (shared Mdm10 subunit) [ 83 ]. The TOM complex binding site is based on the interaction between Tom22 and Tob37 [ 29 , 81 ] and on the interaction between Tom5 and Tom22. It was found that a small fraction of Tom5 being associated with a TOB/SAM complex promotes the folding of Tom40 during its import to the outer membrane [ 80 , 84 ].…”
Section: Structure and Properties Of The Outer Membrane Protein Import Channelsmentioning
confidence: 99%
See 1 more Smart Citation